MENGENAL AKSARA ARAB MELAYU : SEJARAH DAN PERKEMBANGANNYA - Nahlia Turka; Sri Mawaddah (Adisam Publisher, 2025)
Malay Arabic script is one of the written cultural heritages that has played an important role in the history of Malay civilisation, particularly in Southeast Asia. This script developed as a result of interaction between local cultures and Islamic influences that entered the archipelago through trade, missionary work, and education. Throughout its history, the Malay Arabic script has not only served as a means of communication but also as the primary medium for the dissemination of Islamic teachings and the formation of the cultural identity of the Malay people. This study aims to explore in depth the origins, development, role, challenges, and efforts to preserve the Malay Arabic script in the modern era. This study employs a descriptive qualitative approach by examining various scientific literature, journals, and relevant historical documents. The results of the study show that Arabic Malay script has undergone significant development in various aspects of life, ranging from education and literature to royal administration. In addition, this script also played a major role in shaping the cultural and Islamic identity of the Malay community. However, with the development of technology and the dominance of the Latin script, the existence of Arabic Malay script began to be marginalised. Therefore, strategic and sustainable efforts are needed from various parties, such as educational institutions, the government, and cultural communities, to preserve and maintain the existence of this script so that it does not disappear from the nation's cultural heritage.